Cooperative targeting of NF-κB enhances ferroptosis-driven HCC therapy with Alisertib and Donafenib - Zhou, Qiong; Wang, Rui (Frontiers in Cell and Developmental Biology, 2025)
BackgroundHepatocellular carcinoma (HCC) is a major cause of cancer-related mortality worldwide. It is often diagnosed at advanced stages, which limits treatment options. Although Donafenib is a standard therapy for advanced HCC, its effectiveness is often reduced by treatment failures. Alisertib, an Aurora-A kinase inhibitor, shows promise in enhancing the cytotoxic effects of Donafenib. This study investigates the combined therapeutic effects of these two agents.MethodsSynergistic cytotoxicity was assessed via CCK-8 and colony formation assays. Ferroptosis activation was quantified through flow cytometry, lipid peroxidation, and measurements of reactive oxygen species (ROS), intracellular Fe2+, and GSH/GSSG. Mechanistic studies involved immunofluorescence for NF-κB/p65 localization, along with Western blotting, qPCR, and dual-luciferase reporter assays to evaluate protein and gene expression. Chromatin immunoprecipitation (ChIP) experiments were performed to analyze the binding of NF-κB/p65 to its endogenous promoters. In vivo xenografts were established to evaluate the antitumor efficacy and potential side effects of the combination treatment, supported by histological and immunohistochemical analyses.ResultsOptimal synergistic concentrations (Alisertib 2.5 µM + Donafenib 10 µM for HCCLM3; 5 µM for Huh7) induced profound ferroptotic cascades, evidenced by elevated ROS, lipid peroxides, and Fe2+ accumulation concurrent with GSH depletion. The co-treatment potently inhibited p65 nuclear translocation while stabilizing IκBα, thereby suppressing NRF2-mediated antioxidant transcription. Xenograft models demonstrated marked tumor volume reduction with preserved organ architecture and hematological parameters, confirming clinical translatability.ConclusionAlisertib is identified as a potent enhancer of Donafenib-induced ferroptosis through inhibition of the NF-κB/NRF2 pathway. This suggests a novel combinatorial strategy that targets ferroptosis through NF-κB inhibition. Further research is needed to translate these promising results into clinical practice.